El espectáculo dramático-festivo del Corpus en la Salamanca del Renacimiento - Framiñán de Miguel, María Jesús, (Colección Escena clásica ;, 2015)
This book traces the panorama of scenic, theatrical and musical activity that, according to its sources, took place in the city of Tormes during the 16th and first decade of 17th century on the occasion of the fun and festive Eucharistic celebration.